Effect of heat treatment on the dispersion and sintering behaviour of tin doped indium oxide powders. Issue 7 (May 2018) - Mei, Fangsheng; Yuan, Tiechui; Li, Ruidi; Qin, Kai; Zhao, Weishang; Jiang, Shaoying
Abstract: Due to the importance of structural uniformity of ITO targets on the properties of ITO films, the untreated and heat treated tin doped indium oxide powders were used to study the effects of four different dispersants on the dispersion behaviour of nanosized ITO powders. The optimum dispersant is NH4 PAA and its optimum amount is 1.00 wt% when the pH value is 9.0. In addition, the effect of the treatment temperature of nanosized ITO powders on the dispersion and sintering behaviour was also studied by SEM, TEM and XRD. The solid loading of ITO slurries and the relative density of the sintered bodies prepared with ITO powders treated at 900 °C could reach 40 vol% (untreated, 25 vol%) and 98.53% (untreated, 95.04%), respectively. The results indicate that the heat treatment of powders at 900 °C allowed obtaining powders from which ITO aqueous suspensions with high solid loading could be prepared and dense bodies after sintering. In another word, the appropriate heat treatment process for tin doped indium oxide powders could reduce the sintering temperature by 50 ℃ and refine the grain size.